CANADA – FEED-IN TARIFF: ARE FITS DESIRABLE, OR EVEN LEGAL? A CASE COMMENT - Dalpé, Vincent (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2014)
This article summarizes the World Trade Organization Appelate Body's report in Canada – Feed-in Tariff. It focuses the report's three main issues: (1) the application of the Agreement on Trade-Related Investment Measures' Illustrative List to the minimum required domestic content levels in light of article III:8(a) GATT; (2) the article III:8(a) GATT derogation to a violation of national treatment; and (3) the determination of whether a “benefit” has been conferred under article 1.1(b) of the SCM Agreement. It will mainly be argued that the article III:8(a) analysis is overly simplistic and that the subsidy benefit determination technique employed by the Appelate Body is both overly complex and poorly suited for government-regulated markets. Each of these issues comports novel components: it is the first time the TRIMs Agreement's Illustrative List is applied in relation to an article III:4 GATT violation; it is the first time the article III:8(a) derogation is applied in jurisprudence and the article 1.1(b) of the SCM Agreement's benefit determination gives new perspectives regarding government-created markets. The discussion will ultimately move to an analysis of a possible defence under the GATT XX general Exceptions.